Non-hermitian integrable systems from constant non-invertible solutions of the Yang-Baxter equation - Somnath Maity; Pramod Padmanabhan; Vladimir Korepin (Journal of High Energy Physics)
Abstract We construct invertible spectral parameter dependent Yang-Baxter solutions (R-matrices) by Baxterizing constant non-invertible Yang-Baxter solutions. The solutions are algebraic (representation independent). They are constructed using supersymmetry (SUSY) algebras. The resulting R-matrices are regular leading to local non-hermitian Hamiltonians written in terms of the SUSY generators. As particular examples we Baxterize the 4 × 4 constant non-invertible solutions of Hietarinta leading to nearest-neighbor Hamiltonians. On comparing with the literature we find that two of the models are new. Apart from being non-hermitian, many of them are also non-diagonalizable with interesting spectrums. With appropriate representations of the SUSY generators we obtain spin chains in all local Hilbert space dimensions.